1984
DOI: 10.1021/ma00134a051
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of syndiotactic poly(methyl methacrylate) in dilute solutions

Abstract: A combination of several methods and quantitative parameters (fraction p of immobilized monomer units, apparent molecular weight, and size, number, and concentration of aggregates) as a function of time, temperature, and polymer concentration were used to obtain data characterizing aggregation of syndiotactic poly(methyl methacrylate) in n-butyl acetate. The thermal history of the sample (viz., the content of surviving nuclei which were identified with aggregates of globules formed during the intramolecular co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 7 publications
1
20
0
1
Order By: Relevance
“…This principal observation has already been made by Spevacek et al [18,19] when studying the aggregation of polymethylacrylates and was further used by different groups [20,21] in polymer NMR, but to the best of our knowledge not for the detection of the gelation point. Decreasing signal intensity of organogelator molecules in the gel state has also been described by Escuder et al [22] Very advanced NMR methods using double quantum methodology have recently been applied to this problem as well.…”
Section: Resultsmentioning
confidence: 75%
“…This principal observation has already been made by Spevacek et al [18,19] when studying the aggregation of polymethylacrylates and was further used by different groups [20,21] in polymer NMR, but to the best of our knowledge not for the detection of the gelation point. Decreasing signal intensity of organogelator molecules in the gel state has also been described by Escuder et al [22] Very advanced NMR methods using double quantum methodology have recently been applied to this problem as well.…”
Section: Resultsmentioning
confidence: 75%
“…WipLirHt (12) A typical Porod plot is given in Figure 3 for the 45 "C system. As expected, a linear variation is obtained which gives (rH2)1I2 = 2.23 nm.…”
Section: Resultsmentioning
confidence: 99%
“…40 Stereoregular poly(methyl methacrylate)s, (s-PMMA)s have a strong tendency to form the ordered aggregated structures in solution. [41][42][43][44][45] In addition to aggregates of the socalled stereocomplex of PMMA which arise on mixing solutions of isotactic and syndiotactic (PMMA)s, attention has been devoted in recent years to the self-aggregation of s-PMMA alone, using NMR and infrared spectroscopy. It was found that the rate of self-aggregation increases with decreasing temperature and with increasing concentration of the solution.…”
Section: Atactic Pmma/n-butyl Chloride Systemmentioning
confidence: 99%